HUBUNGAN ANTARA SYSTEM REWARD DENGAN KINERJA PERAWAT DALAM MELAKSANAKAN ASUHAN KEPERAWATAN DI RSUD SRAGEN - Sri Rahayu; Enita Dewi (Jurnal Berita Ilmu Keperawatan, 2009)
Background: Arrangement of appreciation system to nurses in Indonesia expected to pay attention to the level of effort and job weight rendered by nurse in executing service or professional nursing care. For a while that happened at General Hospital of Sragen is inequitable incentive division, there are no career development, so that felt concerned about will influence the result of nursing care quality. Objective: This Research target is to know the relation between reward system with the nurse performance in executing nursing care at General Hospital of Sragen. Method: This Research represent non eksperimental quantitative, corelational descriptive methode with cross sectional approach and chi square test use. The intake of sample by total sampling that is as much 73 implementer nurses, bachelor degree and the government worker. Research data concerning reward system and nurse performance in executing nursing care obtained by cuesioner given directly to responders. Result: Result of statistical test with the test of Chi Square obtained p value equal to 0,244 ( p value > 0,05) meaning there are no relation between reward system with the nurse performance in executing nursing care at General Hospital of Sragen. Result of this research indicate that the financial reward is not matter influencing nurse performance in executing nursing care. Conclusion: No relation between reward system with the nurse performance in executing nursing care at General Hospital of Sragen. This results indication that need furthermore research about nurse performance in executing related to nursing care by non financial reward.